Measurement of 1-ps soft-x-ray laser pulses from an injection-seeded plasma amplifier - Wang, Y. (2009)
We report on a pulsewidth measurement of phase-coherent soft x-ray laser pulses generated by injection seeding a solid-target plasma amplifier with high harmonic pulses. A pulse duration of 1.13±0.47 ps was measured for a seeded Ne-like Ti plasma amplifier operating at 32.6 nm using an ultrafast streak camera. This is the shortest pulse duration reported to date from a table-top soft x-ray laser amplifier. The result agrees with model simulations which suggest that intense femtosecond soft x-ray laser pulses could be obtained by injection seeding a tailored plasma amplifier in which the gain is confined to a high density region.